Optimizing Zinc Selenide and Silicon-Based Heterojunction Solar Cells for Enhanced Photovoltaic Performance - Laouid, Amina; Alaoui Belghiti, Amine; Abouais, Ali; Wisniewski, Krzysztof; Tlemçani, Mouhaydine; Płóciennik, Przemysław; Hajjaji, Abdelowahed; Zawadzka, Anna (Solar (MDPI), 2025)
In the purpose of enhancing solar cell efficiency and sustainability, zinc selenide (ZnSe) and silicon (Si) play indispensable roles, offering a compelling combination of stability and transparency while also highlighting their abundant availability. This study utilizes the SCAPS_1D tool to explore diverse heterojunction setups, aiming to solve the nuanced correlation between key parameters and photovoltaic performance, therefore contributing significantly to the advancement of sustainable energy solutions. Exploring the performance analysis of heterojunction solar cell configurations employing ZnSe and Si elements, various configurations including SnO2/ZnSe/p_Si/p+_Si, SnO2/CdS/p_Si/p+_Si, TiO2/ZnSe/p_Si/p+_Si, and TiO2/CdS/p_Si/p+_Si are investigated, delving into parameters such as back surface field thickness (BSF), doping concentration, operating temperature, absorber layer properties, electron transport layer properties, interface defects, series and shunt resistance. Among these configurations, the SnO2/ZnSe/p_Si/p+_Si configuration with a doping concentration of 1019 cm−3 and a BSF thickness of 2 μm, illustrates a remarkable conversion efficiency of 22.82%, a short circuit current density (Jsc) of 40.33 mA/cm2, an open circuit voltage (Voc) of 0.73 V, and a fill factor (FF) of 77.05%. Its environmentally friendly attributes position it as a promising contender for advanced photovoltaic applications. This work emphasizes the critical role of parameter optimization in propelling solar cell technologies toward heightened efficiency and sustainability.
Keywords: heterostructure; SCAPS; ZnSe; CdS; SnO2; TiO2